U.S. Engineering in a Global Economy 2018
DOI: 10.7208/chicago/9780226468471.003.0005
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gaps between Engineering Education and Practice

Abstract: Increasingly, American engineers contend with challenges at work including rapid technological innovation and the needs of changing workplaces (Duderstadt 2008; National Academy of Engineering 2008b; National Research Council 2007). In response, industry, government, and professional societies have called on educators to better prepare engineering students by emphasizing not only technical but professional competencies (Jamieson and Lohmann 2009; Sheppard et al. 2008; Shuman, Besterfield-Sacre, and McGourty 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 25 publications
(42 reference statements)
0
51
0
1
Order By: Relevance
“…As observed by Brunhaver et al [9], it has been found in a survey that 40% of the employees working in engineering projects feel that they are not appropriately skilled or trained for the roles that they have been assigned. To identify the skill gaps, it is essential to analyse the skills that are the most important in such roles.…”
Section: Skills Gap Overviewmentioning
confidence: 94%
“…As observed by Brunhaver et al [9], it has been found in a survey that 40% of the employees working in engineering projects feel that they are not appropriately skilled or trained for the roles that they have been assigned. To identify the skill gaps, it is essential to analyse the skills that are the most important in such roles.…”
Section: Skills Gap Overviewmentioning
confidence: 94%
“…First, the discourse of grit is fundamentally about teaching students to accept and function within the status quo. In engineering education, the status quo has been critiqued on many fronts, from generating a lack of interest in public welfare concerns (Cech, 2014) and empathy (Walther et al, 2020), to having a very narrow sense of ethics (Foley & Gibbs, 2019), to having a culture of stress (Jensen & Cross, 2021), to being racist/raced, sexist/gendered, and ableist (Beddoes, 2012(Beddoes, , 2019Holly, 2020;McCall et al, 2020;Mills et al, 2010;Pawley, 2019;Riley, 2008), to not adequately preparing students for the workplace (Brunhaver et al, 2018), among other things. Grit fundamentally normalises those aspects of engineering education by not challenging them and teaching students they should adapt to them.…”
Section: Contributing To Lack Of Change In Diversity Equity and Inclu...mentioning
confidence: 99%
“…Despite the fact that there is a consensus regarding teamwork as an essential component of engineering education [3][4][5]17] teamwork skills seem hard to define [18,19]. Engineering faculty tend to teach teamwork skills in less structured ways than other constructs such as effective communication [19].…”
Section: Teamwork As a Learning Outcome For Engineering Educationmentioning
confidence: 99%